FAKTOR-FAKTOR YANG MEMPENGARUHI PENYEBAB KECEMASAN PADA PASIEN COVID-19 DI RUANGAN ISOLASI RUMAH SAKIT MURNI TEGUH - Melda Y. Simorangkir; Hendry Kiswanto Mendrofa (Indonesian Trust Nursing Journal, 2026)
The COVID-19 disease is a pandemic disease that has spread to many countries and has claimed many lives. Infected patients will experience several symptoms including fever, acute respiratory distress (cough and shortness of breath). In severe cases, the virus can cause pneumonia, acute respiratory syndrome. kidney failure and death. Which cause the patient to feel anxious about his life. Anxiety is very often experienced by people who are sick, especially COVID-19 patients. This situation causes psychopathological symptoms that indirectly cause immune system disorders which increase psychological pressure in COVID-19 patients. The patient experiences psychological distress and has symptoms of mental illness which can affect his health and worsen his condition. This study aims to identify the factors that influence the causes of anxiety in COVID-19 patients in the isolation room at Murni Teguh Hospital. The research design used correlation analytic with cross sectional approach and the sample is 73 respondents. Data were collected from September to June 2921. The Hospital Anxiety Depression Scale (HADS) questionnaire was used 10 determine patient anxiety. Data were analyzed using chi-square. In conclusion, there is an effect of age on the causes of anxiety in COVID-19 patients in the isolation room at Murni Teguh Hospital with ap value of 0.044 (p<0.05). There is no influence of educational factors on causes of anxiety among COVID-19 patients with a p-value of 0.084 (p<0.05) and there is no influence of the knowledge factor on the causes of anxiety in COVID-19 patients with ap value of 0.28 (p>0.05). It is suggested, can be used as a reference for all educational parties in order to form and also implement nursing services in reducing the level of anxiety which is one of the applicable educational systems.